E-009 Image based geometric characterization of aortic and supra aortic vessels for endovascular access in acute stroke. (23rd July 2017) - BLANC, R; Ciccio, G; Smajda, S; Redjem, H; Desilles, J; Fahed, R; Mazighi, M; Roux, P; Piotin, M
Abstract : Background and Purpose: Fast, safe and stable endovascular access is crucial for mechanical thrombectomy in acute ischemic stroke. We investigated the feasability of a MRI based anatomic and geometric characterization of aortic arch and supra-aortic vessels and correlated these findings with time metrics to access the clot in patients treated for a large intracranial vessel occlusion. Methods: Patients with MRA as a part of the diagnostic imaging in the settings of an acute ischemic stroke by middle cerebral artery occlusion were included. Level Set segmentation of DICOM MRI Datasets was used to create 3D geometric model (surface mesh and centerlines) and automatic analysis of parameters known to affect the endovascular access to intracranial vasculature: Aortic arch Classification; length of carotid arteries from ostium to intracranial carotid termination, tortuosity indexes, angle of take off of left common carotid artery and brachiocephalic trunk (BCT) from aortic arch (AA) and number of changes of direction along the path of the vessel (reverse curves). Those parameters were correlated with time from femoral puncture to clot contact. Results: Analyses were performed in 27 patients. Aortic arch type were I: 17 patients, II: 5 patients and III: 5 patients. Mean length of carotid arteries from ostium to intracranial carotid termination was 285 mm for left side and 299 mm for right side (Including BCT). Mean tortuosity indexes were 1.32 on the left and 1.36 on the right side, mean take off angles of arteries from AA were 109 for the left and 123 for BCT, number of reverse curves were found 12/27 on left side and 15/27 on right side. Length of procedures was impacted by aortic arch type. Conclusion: MRI based morphometric characterization of factors affecting endovascular access to the intracranial circulation is feasible in the settings of acute ischemic stroke imaging and could be helpful for interventional procedures or future developments of vascular access devices. Disclosures: R. Blanc: None. G. Ciccio: None. S. Smajda: None. H. Redjem: None. J. Desilles: None. R. Fahed: None. M. Mazighi: None. P. Roux: None. M. Piotin: None.